Impact of the appropriations on the budget act public (2016)
The national Government is the guarantor of peaceful coexistence and good relations among citizens, in such sense has an excellent economic tool that allows the collection of national income through public resources, so that all citizens are conviernte in the backbone of the economy of the country, in this way Ministry of finance, are confronted in a scenario to elaborate complex bastate programming and implementation of the PGN. Is important mention that them steps public generate commitments of sustainability and operation for all a device state and that is duty of the Government national meet them needs basic of the society in general, for this work the (PGN), must be devoted low principles of specialty, legality, universality, annuity, programming, integrity, exclusivity, unit, periodicity, continuity, flexibility and balance. In addition, you must run the PGN during a tax period, within a framework of legality complying with development plans approved by the Congress of the Republic, in order to give compliance and carrying out the law of appropriations that will be issued before the end of the current year and covering the entire budget meeting to be distributed during the next term in the three major budget categories , transfers, investment and operating costs.